Aqueous extract of Eucalyptus globulus Labill. in the germination and development of Andean crops: a study of allelopathy in Cusco, Perú - Gil-Mora , Juan Eduardo (2023)
Allelopathy is defined as the detrimental effect that one plant causes to another through chemical compounds that are released into the environment; in Peru, the most used species in plantations is Eucalyptus globulus Labill.; despite the recognized utility for various uses in the Andean zone; during the last decades there have been criticisms based on scientific, ecological and emotional arguments, which maintain that eucalyptus deteriorates the soil and water sources; considering these assertions, allelopathy was evaluated through bioassays with aqueous extract of eucalyptus from plantations in four provinces of Cusco: Anta, Calca, Cusco y Quispicanchi; through allelopathy tests carried out with aqueous extract of leaves, tender branches and fruits of Eucalyptus in the germination and growth of seedlings of Amaranthus caudatus L. (kiwicha), Chenopodium quinoa Willd. (quínua), Hordeum vulgare L. (cebada), Vicia faba L. (haba) and Zea mays Vell. and carried out at concentrations of 10; 25; 50; 100 and 1000 mg/L and for the control test, distilled water was used; for the analysis of the information obtained on allelopathy, the TREND software was used, using three trend methods: Student’s T test, Spearman’s test and linear regression. The concentrations to which the five species of Andean crops were subjected did not inhibit the germination of the seeds, nor the development of the seedlings, nor did they affect the length and weight with respect to the control; therefore, it is inferred that the aqueous extract of eucalyptus does not inhibit the development of monocots (corn and barley), nor does it inhibit dicots (broad bean, quinoa and kiwicha). Consequently, the allelopathic effects generated by eucalyptus in crops of broad bean, corn, barley, quinoa and kiwicha are null in bioassays at different concentrations with aqueous extract, not causing allelopathic effects that can inhibit seed germination or plant growth. Seedlings, so it is concluded that Eucalyptus globulus does not produce allelopathy. In Peru and Cusco, E. globulus has been used for reforestation and therefore it is important to know the ecological impact that its allelochemicals have on the soil, since they can affect native flora and fauna.